2021
DOI: 10.3389/fphar.2021.738590
|View full text |Cite
|
Sign up to set email alerts
|

Clemastine Ameliorates Perioperative Neurocognitive Disorder in Aged Mice Caused by Anesthesia and Surgery

Abstract: Perioperative neurocognitive disorder (PND) leads to progressive deterioration of cognitive function, especially in aged patients. Demyelination is closely associated with cognitive dysfunction. However, the relationship between PND and demyelination remains unclear. Here we showed that demyelination was related to the pathogenesis of PND. Clemastine, an antihistamine with potency in remyelination, was predicted to have a potential therapeutic effect on PND by next-generation sequencing and bioinformatics in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
(121 reference statements)
0
13
0
Order By: Relevance
“…Firstly, CMap collects transcriptional profiles from human cell lines treated with smallmolecule compounds and we cannot exclude the possibility that restoration of dysregulated gene expression after being treated with drug candidates may not apply to human disease tissues, especially in non-cancerous diseases. Even so, Cmap has been proved useful in predicting potential drug candidates for subsequent experimental validation in some brain diseases including Parkinson's disease (Gao et al, 2014), ischemic stroke (Luo et al, 2019), and perioperative neurocognitive disorder (Wu et al, 2021). Secondly, since GHK was predicted by network-based drug discovery, we cannot exclude the possibility that GHK may show reactivity to additional off-targets besides primary targets, perturb unintended signaling pathways and finally cause side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, CMap collects transcriptional profiles from human cell lines treated with smallmolecule compounds and we cannot exclude the possibility that restoration of dysregulated gene expression after being treated with drug candidates may not apply to human disease tissues, especially in non-cancerous diseases. Even so, Cmap has been proved useful in predicting potential drug candidates for subsequent experimental validation in some brain diseases including Parkinson's disease (Gao et al, 2014), ischemic stroke (Luo et al, 2019), and perioperative neurocognitive disorder (Wu et al, 2021). Secondly, since GHK was predicted by network-based drug discovery, we cannot exclude the possibility that GHK may show reactivity to additional off-targets besides primary targets, perturb unintended signaling pathways and finally cause side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neuroinflammation and oxidative stress influence neurotrophic factors, especially BDNF, which can increase synaptic plasticity and neurogenesis ( Gardiner et al, 2009 ; Wang et al, 2020 ). Our previous studies have shown that the lower level of the synaptic proteins, i.e., PSD95, SYP, and BDNF, is closely related to cognitive impairment ( Wu et al, 2021 ). In the present study, we found that the expression levels of SYP, PSD95, and BDNF were downregulated in the hippocampus of PND mice, and TNIL treatment ameliorated these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four hours after NOR test, mice were subjected to Barnes maze to test their short-term and long-term spatial learning and memory as previous studies ( Wu W. et al, 2021 ). Barnes maze is a circular platform with 20 equally spaced holes (Anhui Zhenghua Biological Instrument equipments Co., Ltd., Anhui, China).…”
Section: Methodsmentioning
confidence: 99%